2021
DOI: 10.3390/ijms22094384
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Survival Influential Genes in Carcinogenesis

Abstract: The genes influencing cancer patient mortality have been studied by survival analysis for many years. However, most studies utilized them only to support their findings associated with patient prognosis: their roles in carcinogenesis have not yet been revealed. Herein, we applied an in silico approach, integrating the Cox regression model with effect size estimated by the Monte Carlo algorithm, to screen survival-influential genes in more than 6000 tumor samples across 16 cancer types. We observed that the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Subsequently, to further understand the roles of voted genes in cancer progression, we explore their impact on patient survival using a pan-cancer survival influential gene set compiled by our previous study [ 59 ]. We observed that genes linked to poor survival outcomes are significantly overrepresented among the genes identified by the pan-cancer model (24.99%, p -value = 2.56 × 10 –43 , Fisher's exact test).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, to further understand the roles of voted genes in cancer progression, we explore their impact on patient survival using a pan-cancer survival influential gene set compiled by our previous study [ 59 ]. We observed that genes linked to poor survival outcomes are significantly overrepresented among the genes identified by the pan-cancer model (24.99%, p -value = 2.56 × 10 –43 , Fisher's exact test).…”
Section: Resultsmentioning
confidence: 99%